Implicações da obesidade induzida pela dieta hiperlipídica na composição molecular e rugosidade superficial do osso cortical - Paiva, Beatriz Vieira de (2019)
The simultaneous increases in obesity around the world seem to be driven mainly by changes in the global food system. Obesity has complex effects on bone metabolism. It is associated with greater bone mineral content which can protect against fracture. Paradoxically, the obesity is related with reduced mechanical properties as a result of high-fat diet (HFD). Micro-CT system, Fourier-transform infrared spectroscopy (FTIR) and Atomic Force Microscopy (AFM) analysis were employed to characterize the microarchitecture, molecular composition and rugosity of cortical bone in a mouse model of High-fat diet-induced obesity. For this, C57BL/6 mice were randomly assigned for 13 weeks to either a control diet-fed (Control) or HFD-fed. HFD mice showed higher body weight (P < 0.05) and Lee obesity index (P < 0.05) compared to control. No significant differences in histomorphometric analysis and microarchitecture compartments of the cortical tibia were observed in HFD and control mice. Besides, HFD promoted reduction (p<0.05) in surface roughness of cortical tibia compared with control. HFD also induced a decrease (p<0.05) in levels of amide II, collagen and carbonate in cortical tibia. In summary, we showed that HFD promotes reduction of surface roughness associated with reduction of organic/inorganic components as amide II, collagen and phosphate, which suggests that both unprecedented ultra-characterizations can provide novel insight into the HFD/obesity-related compromised bone molecular composition and surface roughness.